Antibiotic Resistance in an Indian Rural Community: A ‘One-Health’ Observational Study on Commensal Coliform from Humans, Animals, and Water - Purohit, Manju Raj (Int J Environ Res Public Health, 2017)
Antibiotic-resistant bacteria are an escalating grim menace to global public health. Our aim is to phenotype and genotype antibiotic-resistant commensal Escherichia coli (E. coli) from humans, animals, and water from the same community with a ‘one-health’ approach. The samples were collected from a village belonging to demographic surveillance site of Ruxmaniben Deepchand (R.D.) Gardi Medical College Ujjain, Central India. Commensal coliforms from stool samples from children aged 1–3 years and their environment (animals, drinking water from children's households, common source- and waste-water) were studied for antibiotic susceptibility and plasmid-encoded resistance genes. E. coli isolates from human (n = 127), animal (n = 21), waste- (n = 12), source- (n = 10), and household drinking water (n = 122) carried 70%, 29%, 41%, 30%, and 30% multi-drug resistance, respectively. Extended spectrum beta-lactamase (ESBL) producers were 57% in human and 23% in environmental isolates. Co-resistance was frequent in penicillin, cephalosporin, and quinolone. Antibiotic-resistance genes bla(CTX-M-9) and qnrS were most frequent. Group D-type isolates with resistance genes were mainly from humans and wastewater. Colistin resistance, or the mcr-1 gene, was not detected. The frequency of resistance, co-resistance, and resistant genes are high and similar in coliforms from humans and their environment. This emphasizes the need to mitigate antibiotic resistance with a ‘one-health’ approach.